2015
DOI: 10.1002/cmdc.201500393
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of the Selectivity of 3‐Benzyluracil‐1‐acetic Acids toward Human Enzymes Aldose Reductase and AKR1B10

Abstract: The human enzymes aldose reductase (AR) and AKR1B10 have been thoroughly explored in terms of their roles in diabetes, inflammatory disorders, and cancer. In this study we identified two new lead compounds, 2-(3-(4-chloro-3-nitrobenzyl)-2,4-dioxo-3,4-dihydropyrimidin-1(2H)-yl)acetic acid (JF0048, 3) and 2-(2,4-dioxo-3-(2,3,4,5-tetrabromo-6-methoxybenzyl)-3,4-dihydropyrimidin-1(2H)-yl)acetic acid (JF0049, 4), which selectively target these enzymes. Although 3 and 4 share the 3-benzyluracil-1-acetic acid scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 86 publications
(73 reference statements)
0
28
0
Order By: Relevance
“…The polyhalogenated compound is characterized as a novel lead, a tetrafluorophenol moiety that targets both AKR1B10 and AR. The same group also solved the methylated AKR1B10K125R/V301L-sulindac complex, which showed that sulindac ( 34 ) and its sulfone might be a drug lead for selective AKR1B10 and AR inhibitors [32], and the methylated AKR1B10K125R/V301L-JF0049, which explained that the selectivity of JF0049 ( 30 ) for AKR1B10 is probably due to its bulkier aryl moiety that cannot occupy the AR specificity pocket but fitting into the larger AKR1B10 active site, including a subpocket defined by loop A that does not exist in AR [36]. These studies collectively pave the way for future efforts in structure-guided drug discovery to target AKR1B10.…”
Section: Structure Of Akr1b10-inhibitor Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyhalogenated compound is characterized as a novel lead, a tetrafluorophenol moiety that targets both AKR1B10 and AR. The same group also solved the methylated AKR1B10K125R/V301L-sulindac complex, which showed that sulindac ( 34 ) and its sulfone might be a drug lead for selective AKR1B10 and AR inhibitors [32], and the methylated AKR1B10K125R/V301L-JF0049, which explained that the selectivity of JF0049 ( 30 ) for AKR1B10 is probably due to its bulkier aryl moiety that cannot occupy the AR specificity pocket but fitting into the larger AKR1B10 active site, including a subpocket defined by loop A that does not exist in AR [36]. These studies collectively pave the way for future efforts in structure-guided drug discovery to target AKR1B10.…”
Section: Structure Of Akr1b10-inhibitor Complexesmentioning
confidence: 99%
“…the acidic phenol) [35]. JF0049 is found to be selective for AKR1B10, which is probably due to its bulkier aryl moiety unable to occupy the AR specificity pocket and its improved fitting into the larger AKR1B10 active site, including a 
subpocket defined by loop A [36]. The application of 
5-carboxymethyl-3-mercapto-1,2,4-triazino-[5,6-B]indoles (WO2015057175) [121], and drug composition containing this compounds was due to their ability to inhibit AKR1B1 and AKR1B10.…”
Section: Akr1b10 Inhibitorsmentioning
confidence: 99%
“…It can be used as a selective inhibitor of AKR1B10. Newly, two synthesized polyhalogenated compound 2,2 ,3,3 ,5,5 ,6,6 -octafluoro-4,4 -biphenyldiol (JF0064, 29) and 2-(2,4-dioxo-3-(2,3,4,5-tetrabromo-6-methoxybenzyl)-3,4-dihydropyrimidin-1(2H)-yl) acetic acid (JF0049, 30) were reported to be potent AKR1B10 inhibitors [35,36]. JF0064 is a non-competitive inhibitor for both AR and AKR1B10.…”
Section: Non-drug Synthetic Compoundsmentioning
confidence: 99%
“…The development of potent and selective AKR1B10 inhibitor as anticancer drugs has attracted growing attentions. Recently, many AKR1B10 inhibitors have been developed rapidly [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. We here, review the recent publications and patents related to AKR1B10 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…This modification has been characterized by enzymatic assays after exposition of hAR in solution under different irradiation doses, by monitoring the progressive structural changes of hAR crystals as irradiation dose increases and by characterizing the structural changes in solution using mass spectrometry. The activity of the in-vitro potent ARIs Zenarestat 30 , JF0048 31 , Epalrestat 32 and Tolrestat 33 was also checked at different irradiation doses. A mechanism for the activation of hAR under oxidative stress conditions is proposed and some suggestions for the structure-based drug design targeting hAR are provided.…”
Section: Introductionmentioning
confidence: 99%